1974
DOI: 10.1161/01.res.34.1.112
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hematocrit and Colloid-Induced Changes in Blood Viscosity on Renal Hemodynamics and Renin Release in the Dog

Abstract: This study compared the effects on the kidney of two major determinants of blood viscosity, the hematocrit and the plasma colloid content. In anesthetized dogs, blood viscosity was raised 30% by increasing hematocrit or infusing isoncotic Dextran 500 while blood volume was kept constant. Neither form of hyperviscosity altered blood pressure, but both forms caused a decrease of about 35% in cardiac output and a comparable rise in total peripheral resistance. Renal blood flow decreased minimally (<10%) in the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1976
1976
1992
1992

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…Although vasopressin release occurred in these animals, it is also possible that portal vein constriction could have affected renal water excretion by altering the metabolic clearance rate of vasopressin. Since TIVC constriction lowered cardiac output and arterial pressure at least as much as, but increased PVP less than the portal venous constriction, it seems likely that the changes in systemic hemodynamics primarily stimulated the release of vasopressin during acute PVP elevations (20). This interpretation is compatible with our previous observation that vasopressin release associated with TIVC constriction is baroreceptor mediated (21).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Although vasopressin release occurred in these animals, it is also possible that portal vein constriction could have affected renal water excretion by altering the metabolic clearance rate of vasopressin. Since TIVC constriction lowered cardiac output and arterial pressure at least as much as, but increased PVP less than the portal venous constriction, it seems likely that the changes in systemic hemodynamics primarily stimulated the release of vasopressin during acute PVP elevations (20). This interpretation is compatible with our previous observation that vasopressin release associated with TIVC constriction is baroreceptor mediated (21).…”
Section: Resultssupporting
confidence: 88%
“…Renin was measured by radioimmunoassay (19) and individual kidney renin secretory rates were calculated by multiplying the difference between renal venous and aortic renin concentrations times renal plasma flow (20). A renin unit is arbitrarily defined as the amount of plasma renin activity necessary to generate 1 ng of angiotensin I in 1 ml plasma during 1 h of incubation at 37°C (20). Animals were administered 0.5-0.8 liters of 2.5%o dextrose at 10-15 ml/min before the experiments to produce stable, hypotonic urine flow rates.…”
Section: Methodsmentioning
confidence: 99%
“…A promising technical advance is the use of freeze-clamped tissue for statistical modelling, 1 * 4 three-dimensional metabolic studies, 1 " and stereology. 16 " Quantitative morphometry is presently limited by the tedium of data collection, and would be enormously facilitated by the development of automated, computer-assisted systems for length detection and pattern analysis. Such equipment would permit application of modern statistical techniques 1 * 3 ' m to the microcirculation.…”
Section: Capillary Diffusionmentioning
confidence: 99%
“…McDonald [10] showed that raising blood viscosity by This study was supported by a Turkish Scientific and Received: Technical Research Council grant (TAG-677).…”
Section: Introductionmentioning
confidence: 99%